Fundamentals Of Inorganic Substances Basic Classes of Inorganic Compounds Nomenclature - Hamidov Abdullaxon Fayzullayevich (Zien Journals, 2021)
Classification of inorganic chemical reactions. In inorganic chemistry, reactions are distinguished: 1) compounds, 2) decomposition (both may or may not be oxidation-reduction reactions), 3) exchange, 4) exchanges, they are always redox. The following article looks into the basic classes of inorganic compounds.
Keywords: Inorganic; amphoteric; oxide; salt-forming